Differential activation behavior of dermal dendritic cells underlies the strain-specific Th1 responses to single epicutaneous immunization. Issue 3 (December 2016) - Lee, Chih-Hung; Chen, Jau-Shiuh; Chiu, Hsien-Ching; Hong, Chien-Hui; Liu, Ching-Yi; Ta, Yng-Cun; Wang, Li-Fang
Highlights: More dermal dendritic cells with higher activation status migrate into draining lymph nodes of B6 mice compared to BALB/c mice. Dermal dendritic cells of B6 mice have a greater ability to capture protein antigen than those of BALB/c mice. Increasing the activation status or amount of captured antigen in dermal dendritic cells induced a Th1 response in BALB/c mice. Differential activation, but not antigen-capturing ability of dermal dendritic cells between BALB/c and B6 mice is dendritic cell-intrinsic. The differential activation of dermal dendritic cells underlies the strain-specific Th1 responses following epicutaneous immunization. Abstract: Background: Epicutaneous immunization with allergens is an important sensitization route for atopic dermatitis. We recently showed in addition to the Th2 response following single epicutaneous immunization, a remarkable Th1 response is induced in B6 mice, but not in BALB/c mice, mimicking the immune response to allergens in human non-atopics and atopics. Objective: We investigated the underlying mechanisms driving this differential Th1 response between BALB/c and B6 mice. Methods: We characterized dermal dendritic cells by flow cytometric analysis. We measured the induced Th1/Th2 responses by measuring the IFN-γ/IL-13 contents of supernatants of antigen reactivation cultures of lymph node cells. Results: We demonstrate that more dermal dendritic cells with higher activation status migrate into draining lymph nodes of B6 mice compared to BALB/c mice. Dermal dendritic cells of B6 mice have a greater ability to capture protein antigen than those of BALB/c mice. Moreover, increasing the activation status or amount of captured antigen in dermal dendritic cells induced a Th1 response in BALB/c mice. Further, differential activation behavior, but not antigen-capturing ability of dermal dendritic cells between BALB/c and B6 mice is dendritic cell-intrinsic. Conclusion: These results show that the differential activation behavior of dermal dendritic cells underlies the strain-specific Th1 responses following single epicutaneous immunization. Furthermore, our findings highlight the potential differences between human atopics and non-atopics and provide useful information for the prediction and prevention of atopic diseases.